Use of innovative technologies in the organization of independent education - Quvandiqova Mohinur Ilhomiddinovna (Peerian Journals Publishing, 2023)
the digital age has revolutionized various areas of our lives, including education. An increasing number of individuals are turning to innovative technologies to form their own study trips outside the traditional education system. In this article, we will explore the use of the most advanced technologies to organize independent education and the benefits they offer to learners.
Keywords: online; platforms; Independent Education